Migration of the Anterior Spinal Rod to the Right Thigh, a Rare Complication of Anterior Spinal Instrumentations: A Case Report and a Literature Review - Camino Willhuber Gaston; Taype Zamboni Danilo; Carabelli Guido; Barla Jorge; Sancineto Carlos (Case Reports in Orthopedics)
Posterior and anterior fusion procedures with instrumentation are well-known surgical treatments for scoliosis. Rod migration has been described as unusual complication in anterior spinal instrumentations; migration beyond pelvis is a rare complication. A 32-year-old female presented to the consultant with right thigh pain, rod migration was diagnosed, rod extraction by minimal approach was performed, and spinal instrumentation after nonunion diagnosis was underwent. A rod migration case to the right thigh is presented; this uncommon complication of spinal instrumentation should be ruled out as unusual cause of sudden pain without any other suspicions, and long-term follow-up is important to prevent and diagnose this problem.